2022
DOI: 10.3390/ijerph192013196
|View full text |Cite
|
Sign up to set email alerts
|

Presentations to the Emergency Department for Problems Related to Mental Health: Sex Differences in Adolescents

Abstract: Background: Adolescents aged sixteen to eighteen years are mostly treated in adult emergency departments. In a study at our tertiary adult emergency department (ED) at the University Hospital in Bern (Inselspital), Switzerland, we found that adolescents significantly more often present with psychiatric problems than adults. The study at hand aimed to characterise those adolescents presenting to the ED triaged with a chief complaint regarding mental health. Furthermore, the goal was to assess sex differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…We found that approximately 25% of suicidal adolescents were diagnosed with adjustment disorders. Our results are in line with a Swiss study that described that approximately 20% of adolescents presented to an emergency department with reactions to stress and adjustment disorders ( 29 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that approximately 25% of suicidal adolescents were diagnosed with adjustment disorders. Our results are in line with a Swiss study that described that approximately 20% of adolescents presented to an emergency department with reactions to stress and adjustment disorders ( 29 ).…”
Section: Discussionsupporting
confidence: 93%
“…Especially in mid-adolescence, girls suffer more often from suicidality and show NSSI than boys. The three times higher proportion of cases in our sample may reflect this fact as well as the fact that adolescent cases with acute suicidality were significantly more likely to be girls than adolescent cases without acute suicidality (28,29). We assume (classification of NSSI is not possible using ICD 10) that the diagnoses of superficial injuries/ lesions, for example, at the forearm, are cutting or scratching and intentional self-inflicted injuries which are also more prevalent in girls than in boys (5-7).…”
Section: Sample and Diagnosesmentioning
confidence: 95%
“…Further, we found that 31% of all MH-related ED encounters were DSH-related, of which 37% had extended LOS. Such a high proportion of DSHrelated ED presentations has been reported in several other studies [12,14,28,38]. It is possible that most of the DSH-related presentations would require an urgent triage code (as noted in Table S1, around 81% of DSH-related ED presentations had triage levels 1-3) (Table S1), but it may take longer to organise MH specialist assessments in the ED resulting in extended LOS.…”
Section: Discussionsupporting
confidence: 52%